Norepinephrine promotes triglyceride storage in macrophages via beta2-adrenergic receptor activation - Petkevicius, Kasparas; Bidault, Guillaume; Virtue, Sam; Jenkins, Benjamin; Dierendonck, Xanthe A. M. H. van; Dugourd, Aurélien; Sáez Rodríguez, Julio; Stienstra, Rinke; Koulman, Albert; Vidal-Puig, Antonio (The FASEB journal, 2021)
Tissue-resident macrophages are required for homeostasis, but also contribute to tissue dysfunction in pathophysiological states. The sympathetic neurotransmitter norepinephrine (NE) induces an anti-inflammatory and tissue-reparative phenotype in macrophages. As NE has a well-established role in promoting triglyceride lipolysis in adipocytes, and macrophages accumulate triglyceride droplets in various physiological and disease states, we investigated the effect of NE on primary mouse bone marrow-derived macrophage triglyceride metabolism. Surprisingly, our data show that in contrast to the canonical role of NE in stimulating lipolysis, NE acting via beta2-adrenergic receptors (B2ARs) in macrophages promotes extracellular fatty acid uptake and their storage as triglycerides and reduces free fatty acid release from triglyceride-laden macrophages. We demonstrate that these responses are mediated by a B2AR activation-dependent increase in Hilpda and Dgat1 gene expression and activity. We further show that B2AR activation favors the storage of extracellular polyunsaturated fatty acids. Finally, we present evidence that macrophages isolated from hearts after myocardial injury, for which survival critically depends on leukocyte B2ARs, have a transcriptional signature indicative of a transient triglyceride accumulation. Overall, we describe a novel and unexpected role of NE in promoting triglyceride storage in macrophages that could have potential implications in multiple diseases.
Gesehen am 30.06.2021